The Impact of Traditional Market Relocation on Traders' Income (Case Study at Kampung Lalang Market) - Saputra, M. Ilham; Sembiring, Rahmad (Li Falah: Journal of Islamic Economics and Business, 2025)
This study analyses the impact of the relocation of Kampung Lalang Market on traders' income, focusing on changes before and after the market relocation. The research aims to identify the factors influencing income variation and evaluate the extent to which relocation affects business sustainability. The study employs a qualitative method with a descriptive approach, directly collecting primary data in the field. Data collection techniques include observation, interviews, and documentation. The study found that most traders experienced a decline in income after the relocation, while some reported an increase in income. Key factors influencing income include the location of the new market, facilities, consumer behaviour, traders' adaptability, and government policies. Additionally, the study highlights that inadequate planning and a lack of post-relocation support from the government hinder business sustainability. The study concludes that careful planning and strong post-relocation support are essential to increasing traders' income and ensuring the long-term sustainability of their businesses. These findings have theoretical and practical implications, providing policymakers with insights into the importance of strategic market relocation planning and practical recommendations for traders adapting to new market conditions.